2022
DOI: 10.1051/0004-6361/202243032
|View full text |Cite
|
Sign up to set email alerts
|

Gas distribution from clusters to filaments in IllustrisTNG

Abstract: Matter distribution in the environment of galaxy clusters, from their cores to their connected cosmic filaments, must in principle be related to the underlying cluster physics and its evolutionary state. We aim to investigate how radial and azimuthal distribution of gas is affected by cluster environments and how it can be related to cluster-mass assembly history. We first analysed the radial physical properties of gas (velocity, temperature, and density) around 415 galaxy cluster environments from IllustrisTN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 136 publications
2
8
0
Order By: Relevance
“…These findings are similar to a recent study of multi-phase gas 𝑧 = 0 in the Illustris TNG simulations (Gouin et al 2022), which found that hot gas extends well beyond 𝑅 200𝑐 for galaxy clusters and that both the hot and warm-hot phases beyond 𝑅 200𝑐 include both infalling and outgoing gas.…”
Section: Association With Halossupporting
confidence: 91%
“…These findings are similar to a recent study of multi-phase gas 𝑧 = 0 in the Illustris TNG simulations (Gouin et al 2022), which found that hot gas extends well beyond 𝑅 200𝑐 for galaxy clusters and that both the hot and warm-hot phases beyond 𝑅 200𝑐 include both infalling and outgoing gas.…”
Section: Association With Halossupporting
confidence: 91%
“…While potential inflows and outflows of baryons along these streams will be studied in the second part of this project, we provide in this paper a first exploration of the impact of galaxy connectivity on the specific star formation rate (sSFR), defined as the SFR normalised by galaxy stellar mass. We emphasise that the multi-scale analysis performed in this work is different from previous studies, which have rather focused on how largescale structures, such as groups or clusters, are connected to large-scale cosmic filaments on megaparsec scales (Kraljic et al 2020;Gouin et al 2021Gouin et al , 2022, yielding relevant conclusions on the properties of the cosmic environments where galaxies live, but not on the properties of galaxies themselves. Moreover, we note that this type of study has only recently been enabled through the advent of large-scale hydrodynamical simulations with more robust baryonic models and increasing resolution (e.g., Tremmel et al 2017;Pillepich et al 2019;Dubois et al 2021), and is crucial in order to interpret future observations.…”
Section: Introductionmentioning
confidence: 90%
“…We nevertheless comment on the fact that cluster outskirts are unique environments A160, page 8 of 16 at the intersection between cosmic filaments and clusters, so that galaxies with different histories co-exist in these regions (e.g., galaxies falling through filaments, splash-back galaxies, or galaxies in groups, as studied in Kuchner et al 2022;Borrow et al 2023;Hough et al 2023). In addition, the question of how galaxies are accreted into cluster cores and the physical processes they undergo during their infall is currently under active investigation (e.g., Gouin et al 2022;Kotecha et al 2022;Salerno et al 2022, and references therein). At this stage we can therefore only argue that results in cluster outskirts might be a combined effect of galaxy diversity and interactions in this unique environment, but a study with a larger number of galaxies is required.…”
Section: Connectivity In Different Cosmic Web Environmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the first, the tSZ effect is a direct probe of the cluster pressure profile (Ruppin et al 2018;Ma et al 2021;Pandey et al 2022), baryon abundance (Hernández-Monteagudo et al 2006;Lim et al 2018), and distribution (Le Brun et al 2015;Ma et al 2015;Amodeo et al 2021;Kim et al 2022;Meinke et al 2021;Kim et al 2022). Even the baryons in filaments can be inferred by stacking the tSZ maps of cluster pairs (Muñoz & Loeb 2018;de Graaff et al 2019;Tanimura et al 2019;Gouin et al 2022). Also, it can shed light on constraining the strength of supernova and active galactic nuclei (AGN) feedback (Hojjati et al 2017;Spacek et al 2018;Gatti et al 2022;Chen et al 2023).…”
Section: Introductionmentioning
confidence: 99%